Social Construction of Gender Equality in the Family of Working Couples in Tanjungbalai Indonesia: An Analysis of Marriage Law and a Compilation of Islamic Law - Heri Firmansyah; Ahmad Fathan Aniq; Rezkia Zahara Lubis (Yayasan Dar Arrisyah Indonesia, 2025)
Gender inequality in working families remains a structural problem in Indonesia. In Tanjungbalai, despite Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI) affirming the equality of husband and wife, patriarchal practices continue to impose multiple domestic responsibilities on women. This study employed a qualitative approach under the paradigm of social definition, using Peter L. Berger’s theory of social construction. Data were gathered through semi-structured interviews with three working families in Tanjungbalai, supplemented by legal document analysis. The findings reveal that the social construction of gender roles is shaped through externalization, objectivation, and internalization institutionalized within community norms. Women continue to shoulder domestic work despite contributing to family income. Meanwhile, the articles within the Marriage Law and KHI are often interpreted in patriarchal terms, thereby reinforcing inequality. The study underscores the need for a gender-responsive reinterpretation of family law and the mainstreaming of gender justice values in household practices. The novelty of this research lies in its integration of Berger’s social construction theory with the legal analysis of Indonesian marriage and Islamic family law, applied to the empirical case of Tanjungbalai—an approach rarely explored in previous scholarship.